Do 'foreigners' pay more? The effects of investor type and nationality on office transaction prices in New York City. Issue 1 (2nd January 2017) - Devaney, Steven; Scofield, David
Abstract: Are commercial real estate prices in metropolitan New York affected by the type or nationality of the investors involved in a transaction? Previous research has highlighted differences in pricing between in-state and out-of-state investors and between different types of investors, but there are few extant studies that consider the influence of nationality on pricing at a micro-level. Foreign investors might pay more than domestic investors for commercial real estate assets because of a lack of information or experience in the market concerned. However, they might use local partners or brokers to mitigate such problems. To explore these issues, we use data provided by Real Capital Analytics on over 3000 office transactions in the New York metro area from 2001 to 2015. We use hedonic regression techniques and propensity score matching to examine whether pricing differs across investor groups after controlling for asset attributes. We find that foreign investors pay more than domestic investors at acquisition, but receive more when selling assets. Tests suggest that it is unmeasured aspects of quality that explain any apparent overpayment for offices in this location, not information issues.